2020
DOI: 10.3390/ijms21186770
|View full text |Cite
|
Sign up to set email alerts
|

On the Way to Understanding the Interplay between the RNA Structure and Functions in Cells: A Genome-Wide Perspective

Abstract: RNAs adopt specific structures in order to perform their biological activities. The structure of RNA is an important layer of gene expression regulation, and can impact a plethora of cellular processes, starting with transcription, RNA processing, and translation, and ending with RNA turnover. The development of high-throughput technologies has enabled a deeper insight into the sophisticated interplay between the structure of the cellular transcriptome and the living cells environment. In this review, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 111 publications
2
25
0
Order By: Relevance
“…In addition, as almost half of the ‐20°C upregulated transcripts were also enriched in P‐bodies (Figure 8d ), it is possible that AU‐rich transcripts enjoy a better protection from degradation at ‐20°C by e.g., some P‐body or EV‐components than the GC‐rich transcripts. Likewise, factors known to influence RNA degradation such as mRNA structure (Akiyama et al., 2016 ; Andrzejewska et al., 2020 ), poly‐A tail length contributing to protective structures at 3′ end (Akiyama et al., 2016 ), and preference of nucleases for certain sequences (Courel et al., 2019 ) should be considered. Gene ontology analysis revealed that the downregulated genes in the ‐20°C group were associated with biological functions of glucose and lipid metabolism and with the compartment of EV (Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as almost half of the ‐20°C upregulated transcripts were also enriched in P‐bodies (Figure 8d ), it is possible that AU‐rich transcripts enjoy a better protection from degradation at ‐20°C by e.g., some P‐body or EV‐components than the GC‐rich transcripts. Likewise, factors known to influence RNA degradation such as mRNA structure (Akiyama et al., 2016 ; Andrzejewska et al., 2020 ), poly‐A tail length contributing to protective structures at 3′ end (Akiyama et al., 2016 ), and preference of nucleases for certain sequences (Courel et al., 2019 ) should be considered. Gene ontology analysis revealed that the downregulated genes in the ‐20°C group were associated with biological functions of glucose and lipid metabolism and with the compartment of EV (Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo structure of Ty1 gRNA or other LTR-retrotransposon transcripts has not been determined. Moreover, as compared to Escherichia coli , plant or mammalian cells, much less is known about the folding of mRNA in yeast ( 34 ). The first transcriptome-wide measurement of yeast mRNA structure was performed in vitro using an enzymatic PARS method (Parallel Analysis of RNA Structure), which suggested that mRNA transcripts with similar biological functions or cellular localization have common structural features ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, we note that the ultimate goal of studying SVRs is to understand the functional roles of RNA structure, which often involves cross-examination of other data sources, including motif analysis of RBPs, multi-omics datasets, etc. Incorporation of these multi-source data may help to accurately annotate SVRs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There are various mature high-throughput SP platforms, such as SHAPE-Seq 7,8 , DMS-Seq 9 , and icSHAPE 10 . These platforms offer flexible options for tackling different biological problems, and have achieved success in uncovering pervasive links between RNA structure and RNA function 11 .…”
Section: Introductionmentioning
confidence: 99%